Strategi Pemasaran Team Betta Concept Dalam Penjualan Ikan Hias Melalui Platform Media Sosial Tiktok - Alfajry, Gefian; Fournawati, Sri Murdilah; Alamsyah, Alamsyah (Social Science Academic, 2023)
This research discusses the marketing strategies adopted by Team Betta Concept in selling ornamental fish, especially betta fish, through the social media platform TikTok. With the development of technology and the popularity of social media, the utilization of platforms like TikTok as a marketing channel has become an attractive trend for businesses in the ornamental fish industry.The research utilizes a qualitative approach with in-depth interviews and content analysis as data collection methods. Through in-depth interviews with members of Team Betta Concept involved in the management and marketing of ornamental fish through TikTok, as well as the analysis of content uploaded on their TikTok accounts, this research identifies and analyzes the marketing strategies implemented by Team Betta Concept.The results of the research show that Team Betta Concept successfully implemented effective marketing strategies in selling ornamental fish through the TikTok platform. These marketing strategies include visually appealing and entertaining content, audience segmentation based on interests and behaviors, and brand positioning highlighting the uniqueness of the betta fish products they offer. In conclusion, this research states that the implementation of Team Betta Concept's marketing strategies in selling ornamental fish through the TikTok social media platform has successfully increased the popularity and attractiveness of their brand. Through an integrated STP (Segmentation, Targeting, and Positioning), Team Betta Concept achieved success in marketing ornamental fish and strengthened their position in the betta fish market. This research provides valuable insights for businesses in the ornamental fish industry and similar industries to understand the marketing potential of TikTok and to adopt more effective marketing strategies in this ever-evolving digital era.